A Study of Fluid Interfaces and Moving Contact Lines Using the Lattice Boltzmann Method (Communications in Computational Physics, 2020)
We study the static and dynamical behavior of the contact line between twofluids and a solid plate by means of the Lattice Boltzmann method (LBM). The different fluid phases and their contact with the plate are simulated by means of standardShan-Chen models. We investigate different regimes and compare the multicomponent vs. the multiphase LBM models near the contact line. A static interface profileis attained with the multiphase model just by balancing the hydrostatic pressure (dueto gravity) with a pressure jump at the bottom. In order to study the same problemwith the multicomponent case we propose and validate an idea of a body force actingonly on one of the two fluid components. In order to reproduce results matching aninfinite bath, boundary conditions at the bath side play a key role. We quantitativelycompare open and wall boundary conditions and study their influence on the shape ofthe meniscus against static and lubrication theory solution.